Deposition of TiC film on titanium for abrasion resistant implant material by ion-enhanced triode plasma CVD - Zhu, Yuhe (2013)
Deposition of titanium carbide (TiC) layer on titanium (Ti) surface has been demonstrated by an ion-enhanced triode plasma chemical vapor deposition (CVD) method using a TiCl4 + CH4 + H2 gas mixture. Physical and mechanical properties of the deposited TiC film on Ti were investigated to examine its potential application as an abrasion resistant implant material. X-ray diffraction (XRD) showed that the specimen was consisted of TiC and Ti. Carbide layer of about 6 μm thickness was observed on the cross section of the specimen by scanning electron microscopy (SEM). The Vickers hardness of surface carbide was more than 2000, which confirmed its high abrasion resistance.